Chaos Synchronization Using Active Control and Backstepping Control: A Comparative Analysis - Vincent, U. E. E. (Nonlinear Analysis: Modelling and Control, 2008)
This paper examines the synchronization performance of two widely used chaos synchronization techniques: active control and backstepping control. It is shown that the two methods have excellent performance, with the active control marginally outperforming the backstepping control in terms of transient analysis. However, the complexity of active controllers suggests that the backstepping control would be more attainable in engineering applications.
Keywords: chaos; synchronization; backstepping; active control